Challenges of Access to Human Rights in the Amazon Context: Ecosystem Insights and Identifying Key Local Players and Initiatives for Legal and Policy Frameworks (Global Journal of Human-Social Science, 2024)
This comprehensive study delves into the multifaceted human rights challenges in the Amazon region focusing on ecosystem insights and identifying key local stakeholders It explores the intricate interplay between environmental concerns and human rights emphasizing the role of indigenous communities NGOs and government bodies The paper proposes innovative legal and policy frameworks to address these issues effectively advocating for integrated strategies that respect the unique socio-cultural and ecological fabric of the Amazon
Keywords: amazon region; human rights; indigenous communities; environmental challenges; ecosystem analysis